Using Cooperative Script Learning in Teaching Listening for physiotherapy study program Students of Second Semester in STIKes Ngudia Husada Madura - Dhaniel Prasetyo Irianto; Amir Hamzah (LPPM IAI Nazhatut Thullab, 2020)
Cooperative Script is the cooperative learning method in which students work in pairs and verbally summarize the parts of the material learned in the classroom. The purpose of the study is to find out the student's response toward using Cooperative Script Learning in teaching listening. In this study, the researcher using descriptive qualitative, and the population was taken from the second-semester physiotherapy program study health students consist of eleven students. To obtain the data, then the researcher applied the following method: Observation sheet, Interview sheet, Questionnaire sheet, and Documentation sheet. The lecturer used a Cooperative script in teaching listening at twice a meeting. For the once, it needed 90 minutes. It was done by teaching listening in some aspects by materials spoof. The student asked how to did it. Then the lecturer asked for the student to practice with their partner by using Part of Body Cavities Text. If students did not understand, the lecturer replied anymore until the students understood truly. Similar research is expected to be conducted in different area and population Key Words: Cooperative Script Learning, Teaching Listening